Sewers in Civilization. The Struggle for the Sanitary Condition of the Human Environment - Yuriy A. Ivanyushin; Marina V. Obuhova; Victor V. Mironov (Журнал Фронтирных Исследований)
This paper is dedicated to the issues of human activity on sanitary ‘frontier’ from antiquity to present. The structure of the article is determined by the initially put forward hypothesis about the unconditional relationship between the stages of civilizational development and technical level of sewers of ‘frontier’ states: centers of science, technology, and culture. We used systemic approach: development of sewerage systems was analyzed chronologically; the importance of environmental engineering “city-river” systems were noted; and the stages of formation of sewers in the largest centers at industrial era, as well as the need for their modernization in connection with deterioration of environmental situation and corresponding demand of society were considered separately. Although contemporary sewer systems are one of the most amazing inventions of mankind, the contradictions inherent to these systems have not yet been resolved on a global scale. The authors conclude that many of the problems that faced the largest cities in developed countries in the past are now facing the capitals and agglomerations of developing countries. Echoes of the medieval unsanitary conditions can be found everywhere in today’s settlements, and sewer systems of the world’s largest industrial centers often correspond to Victorian London in the level of development and perfection. There is an increasing need for a fundamentally new approach to organizing engineering systems while maintaining and, in some cases, increasing the level of hygiene and sanitation. Digital technologies will become increasingly important.